Combination Of Character Change And Utilization Of Social Media As A New Strategy To Maintain SMEs Resilience During The Covid-19 Pandemic - Saiful Aminudin Alkusuma Putra; Heri Pratikto; Agung Winarno (Journal of Business and Management Review, 2021)
This research was motivated by the emergence of the COVID-19 pandemic which spread throughout the world and resulted in a crisis until SMEs went bankrupt. This study aims to investigate how SMEs can face crises and the strategies they have devised to keep their businesses afloat, to prepare SMEs for future crises. The population was SMEs who are members of the Institute for Modern Creative Industries. The sampling technique used a purposive sampling technique with 6 sources. This research is a type of qualitative research with a case study approach. The type of case study used is a collective or multiple case study. This study uses primary data. Data collection techniques used in this study were interviews and observation. The data analysis technique used is a spiral model technique and is assisted by using Nvivo Software 12 for the result of this study, so that SMEs can survive, an entrepreneur must have adaptive and optimistic character because optimism is an inherent trait of all business actors. The strategies used for the survival and resilience of SMEs in times of crisis are advertising and promotion through social media, doing word of mouth, giving attractive discounts, diversifying products, efficiencies such as reducing employee work time, reducing product variety and reducing inventory.